Utilization of Hematite Nanomaterial Based on Geres River Sand Magnetic Mineral to Improve Water Quality - Meiliyadi, Lalu Ahmad Didik; Rahman, Muh. Zainur; Arizona, Kurniawan; Wahyudi, Muh. (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
This study aims to synthesize hematite based on magnetic minerals from the Geres River sand, which is used as a heavy metal absorbent. The Geres River iron sand-based magnetic mineral has a high iron content that can be extracted to produce hematite. The synthesis method used is the coprecipitation method. Mineral content and morphology were characterized using SEM-EDX. Hematite functional groups were analyzed using FTIR. Water quality analysis was based on physical parameters (conductivity and TDS) using a TDS meter, while the heavy metal content of Mn before and after filtration was analyzed using AAS. Based on SEM-EDX analysis, the average grain size of hematite was (0.99 ± 0.20) µm with the highest element content of Fe (72.90 ± 0.28) %. Functional groups are formed at a wavelength of 951.72 cm-1, which shows the Fe=O double bond. After filtration, hematite was able to reduce the heavy metal content of Mn by 19.58%, followed by a decrease in conductivity by 12.95% and a decrease in TDS by 15.18%. This shows that hematite is effectively used as a heavy metal absorbent. Through this research, it is hoped that the community will not only use iron sand magnetic minerals as building materials but also process them into more useful materials such as hematite, which can be used as a heavy metal absorbent.